Status of atmospheric particulate matter and black carbon concentration at Ashuganj in Brahmanbaria - Baitun, Sumaya; Begum, Bilkis Ara; Khan, Md Badiuzzaman (Journal of the Bangladesh Agricultural University, 2018)
Atmospheric particulate matter (PM) samples (both PM10 and PM2.5) were collected simultaneously from Midland Power Company Limited at Ashuganj, in Brahmanbaria to monitor the seasonal fluctuations of particulate matter and black carbon (BC) concentrations from air samples. Total eight samples were collected from January 2016 to December 2017 using two Air Metrics MiniVol samplers and the quantity of PM2.5 and PM10 was detected by weighing the filters before and after exposure. The concentration of PM (PM2.5 and PM10) and BC were analyzed at the laboratory of Chemistry Division, Atomic Energy Centre, Dhaka. The black carbon concentration from both PM2.5 and PM10 samples were also determined by reflectance measurement. The concentrations of PM2.5 varied from 12.2–145 μgm−3 where mean value was 67.09 μgm−3. The mean concentration of PM10 was 103.64 μgm−3 whereas the concentration ranged from 20.5–220 μgm−3. The ratios of PM2.5/PM10 fluctuated during different seasons, winter showed higher concentration and summer showed relatively lower concentration for both PM2.5 and PM10. Atmospheric dispersion due to increased wind speeds and wider mixing layer heights are recognized to be responsible for the lower PM concentrations in warmer months. The concentrations of BC in PM2.5 also varied from 2.44–33.4 μgm−3 and BC in PM10 varied from 4.51–57.2 μgm−3, respectively. The concentrations of particulate matter exceeded the Bangladesh National Ambient Air Quality Standard. J. Bangladesh Agril. Univ. 16(2): 232-236, August 2018 <!–[if gte mso 9]> romij 16.00 <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>